Contaminant organisms recorded on plant product imports to South Africa 1994–2019 - Davina L. Saccaggi (Nature Portfolio, 2021)
Measurement(s) organism Technology Type(s) organism identification assay Sample Characteristic - Organism Plantae Sample Characteristic - Location Republic of South Africa Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13668824